Precompetitive Emotional State of Dancesport Athletes (Baltic Journal of Sport and Health Sciences, 2017)
Background. The paper deals with the precompetitive emotional state of dancesport athletes before competition. Research aim was to analyze pre-competition emotional state of dancesport athletes. Methods. The pre-competition emotional state of dancesport athletes was established using methods of in-depth interview and participant observation. The main reasons for different types of emotional states were identified, and finally, recommendations for athletes and coaches how to overcome immoderate anxiety interfering with good competition results were developed.Results.  Precompetitive  emotional  state  before  competition  may  be  described  as  a  complex  multi-faceted phenomenon which consists of different psychological categories such as: anxiety, arousal, stress, self-confidence, concentration. The results of the interviews and participant observation showed that precompetitive emotional states of the dancesport athletes were both positive and negative. Positive emotional state was shown by the majority of participants. There were found six reasons of positive emotional state and five reasons of negative emotional state as well. Conclusion.  To  overcome  the  negative  emotional  state  or  reinforce  positive  emotional  state  before  the competitions it is suggested to listen to pleasant music, do breathing exercises or do the mental exercise. The choice depends on the personal characteristics of athletes.Keywords: dancesport, precompetitive state, emotions.